Scientific and practical understandings of smart cities. - Moser, Corinne; Wendel, Thomas; Carabias-Hütter, Vicente (My University, 2014)
Smart cities are envisioned to link different fields of action such as mobility; energy production, distribution, and consumption; buildings; governance and stakeholder processes; and urban planning. Information and communication technologies are seen as key to these interconnections. The overall goal of a smart city is to save energy and simultaneously to increase the quality of life for inhabitants. Although a broad variety of descriptions of smart cities have been developed, the concept itself appears to be rather fuzzy and hard to grasp. A clear-cut, common definition of smart cities is still lacking. The goal of this paper is to better understand what a smart city constitutes and what it means from the perspective of science, as well as from a practical point of view. In a thorough literature analysis, we identify different i) definitions, ii) approaches, iii) fields of actions and iv) technologies associated with smart cities. Our analysis is based on interdisciplinary scientific literature, as well as on practical documents (e.g. websites of pilot projects). In a subsequent step, we compare the different understandings of smart cities. In so doing, we focus on similarities and differences between scientific and practical approaches. In a final step, we identify opportunities and challenges arising from the identified similarities and differences. Recognizing these challenges and potentials is of particular interest for so-called transdisciplinary research in urban development, where scientists and practitioners work closely together. Differences between science and practice might on the one hand inform research on smart cities concerning practical implications and experiences. On the other hand, they can also inform practitioners about scientific innovation in urban development (e.g. cloud computing assessing sensor data in real time).
Keywords: Stadtplanung; Stadtentwicklung; Innovation; Technologieeinsatz; Integration; Datenerfassung; Ökologie; Energie; Smart City; Begriff; Steuerung; Planungsansatz; Transformation; Stadtmanagement; Vernetzung; Elektromobilität; Smart Metering; Energieeffizienz; Literaturstudie